Governmental intervention in foreign trade in archaic and classical Greece - Bissa, Errietta M. A. (Mnemosyne, Supplements, 2009)
Trade was a necessity in the ancient Greek world, yet the prevalent scholarly view is that Greek states intervened in foreign trade only rarely and sporadically. This book studies four necessary commodities, gold, silver, ship-building timber and grain, from production through export to import. Through the re-evaluation of known evidence and the presentation of new avenues of research, the book shows that Greek and non-Greek governments in the archaic and classical periods intervened and involved themselves greatly in foreign trade. The book offers the student of the Greek economy a fresh perspective on state intervention in trade and the ways in which intervention worked in the Greek world.